JUMPA Vol.2 No.1 Feb 2015 PENGARUH MERGER DAN AKUISISI TERHADAP KINERJA KEUANGAN PERUSAHAAN: PENGARUH MERGER DAN AKUISISI TERHADAP KINERJA KEUANGAN PERUSAHAAN - Sarwo Edy Handoyo Fakultas Ekonomi Universitas Tarumanagara; Febiana Wahyudi Fakultas Ekonomi Universitas Tarumanagara (Sekolah Tinggi Ilmu Ekonomi Y.A.I - Jakarta - Indonesia, 2015)
This research aims to examine the differences of pre and post merger and acquisition on firm’s performance at Indonesia Stock Exchange. Firm performance is measured using some financial ratios, which are ROA (return on assets), ROE (return on equity), NPM (net profit margin), DR (debt ratio), EPS (earning per share), PER (price earning ratio),TATO (total asset turnover). The samples in this study were 26 manufacturing companies that were taken by purposive sampling method. The analysis used to test the hypothesis of this research is quantitative analysis with statistical methods of data normality test, Paired sample t-test and Wilcoxon signed rank test. The results from the Paired sample t-test and Wilcoxon signed rank test shows that there are no significant difference in testing 2 years before with 2 years after M&A for DR, PER, and TATO in acquiring firm, ROA, ROE, DR, EPS, PER, and TATO in acquired firm, ROA, ROE, NPM, DR, EPS, and PER in surviving firm. There are also significant difference in testing 2 years before with 2 years after for ROA, ROE, NPM, and EPS in acquiring firm, and TATO in surviving firm. These variables should be examined in a longer period of time in order to have better results.